Model Pengembangan Rumpon Sebagai Alat Bantu dalam Pemanfaatan Sumber Daya Ikan Tuna Secara Berkelanjutan - Tri Wiji Nurani; Sugeng Hari Wisudo; Prihatin Ika Wahyuningrum; Risti Endriani Arhatin (Jurnal Ilmu Pertanian Indonesia, 2014)
The increasing use of fish agregating devices (FADs) in the Indian Ocean South Coast of Java is concerned that will be affect the sustainability of tuna resources. The research aimed to evaluate and make development model of FADs as a tool in the sustainability utilization of tuna fish resources. Research was conducted in PPP Tamperan and PPP Pondokdadap. The evaluation was conducted to 1) the lengths size composition, 2) tuna stok resources, 3) map location of FADs, 4) policy rules of use of FADs. Evaluation results indicated 1) the size composition of decent catch tuna fish in PPP Tamperan and PPP Pondokdadap differed for sampling in different month, i.e. respectively in June-July 75,14 and 99,42%, while in August-September 43,18 and 73,43% respectively; 2) estimation of MSY is 2.569 tonnes per year, the optimum effort of 970 units, the level of utilization is 78,81; 3) FADs installed in position 8-13 oLS, 111-113 oBT, the number of FADs quite a lot with the installation distance was less than 10 miles and not in order; 4) regulations already existed, but the level of stakeholder understanding of regulations was still low. Based on evaluation results, recommendations of development model are 1) tightening the permissions, that tuna fish which is allowed to be caught is with lenght size over than 80 cm; 2) FADs installation location refers to the variability of chlorophyll-a, sea surface temperature and the rules that are contained in the Kepmen KP No. 30/2004, 3) more technical regulations need to be made and socialized, accompanied with monitoring and controlling.